Expatriate skills training strategies of Chinese multinationals operating in Australia - Zhang, M.; Fan, David (John Wiley & Sons Ltd., 2014)
Recent years have witnessed a phenomenal growth in outward foreign direct investment (FDI) by Chinese multinationals. In contrast to their developed country counterparts, Chinese multinationals lack experience in foreign expansion and international operation. Although there has been increasing academic attention placed on Chinese outward FDI, little research on expatriate skills training of Chinese multinational enterprises (MNEs) has been conducted. Since the mainstream research focuses on expatriate pre-departure training rather than on learning during assignment, this study aims to bridge this gap by exploring how Chinese MNEs cope with expatriate training and skill enhancement when operating in an advanced economy such as Australia. The study utilises cross-level, in-depth interviews to analyse expatriate training in seven Chinese multinationals. Drawing on social learning theory, some patterns of Chinese expatriate skills training strategies are revealed, such as internationalisation as learning, the use of subsidiaries as a training tool, and learning as belonging.